A Field Study of the Job Stress Faced by Agricultural Employees in the Kirkuk Agriculture Directorate, Iraq - Ekhlas Thaer Mahmood; Ahmed Thwaini Hdoom Al-Salhi; Mahdi Najm Rakhit; Amal Najim Hasan (Andalasian International Journal of Agriculture and Natural Sciences (AIJANS), 2025)
The study aimed primarily to identify the job stress facing agricultural employees in Kirkuk Agriculture Directorate and determine the descending order of each area of study, This was achieved by using a data collection form that included three main areas of job stress: (personal stress, administrative stress, and organizational stress) , The research population consisted of all agricultural employees, totaling (600) agricultural employees in Kirkuk Agriculture Directorate, A random sample of (18%) was taken, comprising (108) agricultural employees ,The research results concluded that organizational stress ranked first in terms of importance, with a weighted mean of (3.41) and a percentage weight of (68.2%), followed by personal stress (3.11, 62.2%), and then administrative stress (3.06, 61.2%). The most prominent sources of stress were: role ambiguity, poor appreciation, lack of professional development opportunities, unfair wages, and high expectations without the necessary resources, Furthermore, continuous exposure to these stress may weaken an employee’s ability to make sound decisions, innovate, and adhere to agricultural quality and safety standards. The study recommends implementing targeted training programs, improving administrative support systems, enhancing communication between leadership and employees, and creating a stimulating and supportive work environment, these steps are essential to ensuring the sustainability and competitiveness of the agricultural sector by maintaining the mental health and professional competence of its workers.